A dodecylamine derivative of cyanocobalamin potently inhibits the activities of cobalamin‐dependent methylmalonyl‐CoA mutase and methionine synthase of Caenorhabditis elegans. Issue 1 (1st August 2014) - Bito, Tomohiro; Yabuta, Yukinori; Ichiyanagi, Tsuyoshi; Kawano, Tsuyoshi; Watanabe, Fumio
Abstract : In this study, we showed that cyanocobalamin dodecylamine, a ribose 5′‐carbamate derivative of cyanocobalamin, was absorbed and accumulated to significant levels by Caenorhabditis elegans and was not further metabolized. The levels of methylmalonic acid and homocysteine, which serve as indicators of cobalamin deficiency, were significantly increased in C. elegans treated with the dodecylamine derivative, indicating severe cobalamin deficiency. Kinetic studies show that the affinity of the cyanocobalamin dodecylamine derivative was greater for two cobalamin‐dependent enzymes, methylmalonyl‐CoA mutase and methionine synthase, compared with their respective coenzymes, suggesting that the dodecylamine derivative inactivated these enzymes. The dodecylamine derivative did not affect the levels of mRNAs encoding these enzymes or those of other proteins involved in intercellular cobalamin metabolism, including methylmalonyl‐CoA mutase ( mmcm ‐ 1 ), methylmalonic acidemia cobalamin A complementation group ( mmaa ‐ 1 ), methylmalonic aciduria cblC type ( cblc ‐ 1 ), and methionine synthase reductase ( mtrr ‐ 1 ). In contrast, the level of the mRNAs encoding cob(I)alamin adenosyltransferase ( mmab ‐ 1 ) was increased significantly and identical to that of cobalamin‐deficient C. elegans . These results indicate that the cyanocobalamin‐dodecylamine derivative acts as a potent inhibitor of cobalamin‐dependent enzymes and induces severe cobalamin deficiency in C. elegans . Abstract : CN‐Cbl dodecylamine, a derivative of cyanocobalamin, was absorbed by C. elegans . CN‐Cbl dodecylamine decreased activities of cobalamin‐dependent enzymes. CN‐Cbl dodecylamine induced cobalamin deficiency in C. elegans . CN‐Cbl dodecylamine acts as an inhibitor of cobalamin‐dependent enzymes.